Fashioning Jews : Clothing, Culture and Commerce (SJC #24) - Greenspoon, Leonard J. (Leonard Jay) (Book collections on Project MUSE., 2013)
This volume presents papers delivered at the 24th Annual Klutznick-Harris Symposium, held at Creighton University in October 2011. The contributors look at all aspects of the intimate relationship between Jews and clothing, through case studies from ancient, medieval, recent, and contemporary history. Papers explore topics ranging from Jewish leadership in the textile industry, through the art of fashion in nineteenth century Vienna, to the use of clothing as a badge of ethnic identity, in both secular and religious contexts.